Free convection to cool a hot square block by embedding in center of a chamber by nanofluid and magnetohydrodynamic. (May 2022) - Sui, Dianjie; Mansir, Ibrahim B.; Gepreel, Khaled A.; Dahari, M.; Nguyen, Dinh Tuyen; Badran, Mohamed Fathy; Van Nguyen, Nhanh; Wae-hayee, Makatar; Zhan, Mingwang
Abstract: Hot block is observed in numerous industries and applications that can being an electronic component, solid matrix, battery, etc. In the present 2D simulation, a uniform magnetic field (MHD model) in the x-direction was utilized to affect the free convection of nanofluid water- A l 2 O 3 for aim of improvement and control the heat transfer and flow characterizations. The used geometry consisted of square chamber and hot block embedded in center of square chamber. The walls of the hot block and chamber performed as hot and cold sources led to create buoyancy force. This study investigated for Varity inclined angles of hot block ( 0 < η < 45 ), Rayleigh numbers ( 10 2 < R a < 10 4 ) and Hartmann numbers ( 0 < H a < 40 ) when the volume fraction of suspension was φ = 0.04 . Also, the effects of the mentioned parameters were studied on the streamlines, temperature contours, average Nusselt number. Observations showed that Adding magnetic field increased the heat transfer rate by 200% At low Rayleigh numbers, but it reduced the heat transfer rate 48% At high Rayleigh numbers.